2011
DOI: 10.1093/brain/awr262
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNA dysregulation in multiple sclerosis favours pro-inflammatory T-cell-mediated autoimmunity

Abstract: Pro-inflammatory T cells mediate autoimmune demyelination in multiple sclerosis. However, the factors driving their development and multiple sclerosis susceptibility are incompletely understood. We investigated how micro-RNAs, newly described as post-transcriptional regulators of gene expression, contribute to pathogenic T-cell differentiation in multiple sclerosis. miR-128 and miR-27b were increased in naïve and miR-340 in memory CD4(+) T cells from patients with multiple sclerosis, inhibiting Th2 cell develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
181
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(192 citation statements)
references
References 55 publications
(67 reference statements)
7
181
1
2
Order By: Relevance
“…As such, these miRNAs may be differentially expressed in other immunemediated diseases and have broader implications on CD4 T cell development and differentiation. It is well established that miRNAs play key roles in the development and function of Tregs (Gao et al, 2012;Josefowicz et al, 2012;Dooley et al, 2013), and differential expression of miRNAs have been found in patients with multiple sclerosis (Du et al, 2009;Keller et al, 2009;Otaegui et al, 2009;De Santis et al, 2010;Guerau-de-Arellano et al, 2011;Noorbakhsh et al, 2011;Jr OeF et al, 2012;Smith et al, 2012;Gandhi et al, 2013;Ridolfi et al, 2013;Søndergaard et al, 2013). To our knowledge none of the miRNAs identified in this study had been previously defined to play a role in Tregs.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…As such, these miRNAs may be differentially expressed in other immunemediated diseases and have broader implications on CD4 T cell development and differentiation. It is well established that miRNAs play key roles in the development and function of Tregs (Gao et al, 2012;Josefowicz et al, 2012;Dooley et al, 2013), and differential expression of miRNAs have been found in patients with multiple sclerosis (Du et al, 2009;Keller et al, 2009;Otaegui et al, 2009;De Santis et al, 2010;Guerau-de-Arellano et al, 2011;Noorbakhsh et al, 2011;Jr OeF et al, 2012;Smith et al, 2012;Gandhi et al, 2013;Ridolfi et al, 2013;Søndergaard et al, 2013). To our knowledge none of the miRNAs identified in this study had been previously defined to play a role in Tregs.…”
Section: Discussionmentioning
confidence: 63%
“…Information on patients with multiple sclerosis and control subjects used in the miRNA profiling study, as well as the methods and data from this miRNA profiling study can be found in Guerau-de-Arellano et al (2011). The data shown in Fig.…”
Section: Human Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the emerging evidence for a pathogenic role of IL-22 in autoimmune processes as well as the importance of small non-coding microRNAs (miRNAs) for the regulation of gene expression in MS (e.g. [8][9][10]), we set out to explore whether the MS association signal at the 3′ end of IL22RA2 may be owing to one or more functional sequence variants in or near miRNA binding sites located in the IL22RA2 3′ untranslated region (UTR). Such variants may alter the binding of certain miRNA(s) to the mRNA 3′UTR and, as a result, the expression levels of IL22RA2.…”
Section: Introductionmentioning
confidence: 99%